The Era of Endless Repatriation: Respectful Relationality and the Reconfiguration of Colonial Authority - Weiss, Joseph (Anthropologica, 2022)
Originally given in the form of two lectures at the Musée du quai Branly, this essay explores the often fraught politica of repatriation in a Canadian context. It suggests that we have moved into an era in which repatriation, understood in this alternate sense as the decentring of settler museum authority and the recognition of Indigenous sovereign rights, is simply unavoidable. This is not just about a “reckoning” with prior histories of colonial appropriation. Rather, it is a recognition of the fact that the structures of settler colonialism themselves are shifting (cf: Kauanui 2016), and museums in such contexts will need to engage with the idea of repatriation as such, as a social phenomenon that entails transformation over the longue durée instead of a set of individual, case by case incidents. Drawing on the author’s experiences as an anthropologist and a curator working with Indigenous Nations on the Northwest Coast of what is now called Canada, the essay ultimately argues that museums will arrive at stronger, more productive relationships with First Peoples by accepting the ongoing reality of repatriations. Indeed, it suggests that it is only through collaboration that genuinely decentres museum authority and foregrounds Indigenous sovereignty that museums will be able to develop genuinely future-oriented and responsible practices.